Markets for Cybercrime Tools and Stolen Data - Ablon, Lillian; Libicki, Martin C.; Golay, Andrea A. (RAND Corporation, 2023)
Criminal activities in cyberspace are increasingly facilitated by burgeoning black markets. This report characterizes these markets and how they have grown into their current state to provide insight into how their existence can harm the information security environment. Understanding these markets lays the groundwork for exploring options to minimize their potentially harmful influence.